Acral Cutaneous Ulcerations and Livedo Reticularis with Rapidly Progressive Interstitial Lung Disease in Anti-MDA5 Antibody-Positive Classical Dermatomyositis - Rachot Wongjirattikarn; Suteeraporn Chaowattanapanit; Charoen Choonhakarn; Apichart So-ngern; Ajanee Mahakkanukrauh; Chingching Foocharoen (Karger Publishers, 2020)
Rapidly progressive interstitial lung disease (RP-ILD) and its distinctive cutaneous features are highly associated with the presence of anti-melanoma differentiation-associated gene 5 (anti-MDA5) antibody in patients with dermatomyositis (DM), leading to a poor prognosis. We describe the case of a 25-year-old man who developed progressive proximal muscle weakness with RP-ILD and had unusual cutaneous findings (cutaneous ulcerations and livedo reticularis) accompanied by classical cutaneous features (heliotrope rash, Gottron's papules, Gottron's sign, and flagellate erythema). Blood test was positive for anti-MDA5 antibody. He was treated with intravenous corticosteroids and immunoglobulin, but passed away due to respiratory failure within 1 month after admission. Our case highlights that the presence of cutaneous ulcerations and livedo reticularis, in addition to RP-ILD, are useful clinical clues that may aid in the detection of anti-MDA5 antibody, early initiation of combined immunosuppressants, and prognosis prediction in patients with classical DM.